Measurement of BER and WLAN strength based on indoor propagation / Mazlina Mansor Hassan … [et al.] - Hassan, Mazlina Mansor; Sheikh Naimullah, Bibi Sarpinah; Ishak, Saurdi; Norily, Juhari (Research Management Institute (RMI), 2012)
A Wireless Local Area Network (WLAN) is a connection to the internet using some wireless distribution methods (typically spread-spectrum or OFDM radio), in which two or more devices are connected through an access point or router. WLAN services gives users the mobility to move around within a local coverage area and still be connected to the network within the same building . Due to ease of installation of WLAN and the increasing popularity of laptop computers, WLAN have become popular to all people in the world. However the WLAN signal strength can change over time. Users cannot obtained a strong signal every time they access the internet. This is due to several factors that can effect the WLAN signal strength performance. One of the factors which affect the WLAN signal strength is the noise which comes from obstacles that exitst in our surrounding. It is also known as Multipath fading. This type of noise is a main problem that exists in mobile communication environment. The signals transmitted via radio channel to receiver propagate in the air, tend to produce a large number of reflected radio waves that arrive at the receiver at different times. This is the result of delayed signals, which are caused from the reflection of signals from walls, tables, or other items. These reflected radio waves interfere with the direct wave and cause intersymbol interference (ISI), which cause significant degradation to the network performance. In order to overcome a multipath fading environment, it is possible to use OFDM transmission scheme. OFDM is based on parallel data transmission scheme that reduces the effects of multipath fading and renders complex equalizers unnecessary. This project will study and identify the Orthogonal Frequency Division Multiplexing (OFDM) technology that gives the best BER performance in a multipath fading environment and compare BER performance using different modulation techniques in MATLAB.